Analisis Kapasitas Mesin Perebusan Menggunakan Metode Rought Cut Capacity Planning Pada Pt. Anugrah Fajar Rezeki - Jaya Pratama, Agam; Nadia, Yusri (Program Studi Teknik Industri, Fakultas Teknik. Universitas Samudra, 2023)
Abstract- This study aims to analyze the capacity of the boiling machine at PT. Anugrah Fajar Rezeki by applying the Rough Cut Capacity Planning (RCCP) method. Optimal machine performance is very important in the production process, considering that the machine functions as an aid in processing raw materials into finished products. Through the RCCP method, this study found that the two available boiling machines have a capacity of 30 tons per hour each and can produce a total of 1,440,000 kg of boiled per day. The results of the analysis show that the capacity of the machine can meet existing production needs. However, to improve efficiency and productivity, it is recommended that the company implement a periodic performance monitoring and evaluation system and conduct training for employees on more efficient production techniques. With this recommendation, it is hoped that PT. Anugrah Fajar Rezeki can improve operational performance and meet the growing market demand.